A framework for constructing elasto‐plastic constitutive models for frozen and unfrozen soils. (14th December 2021) - Yu, Fan; Guo, Peijun; Na, SeonHong
Abstract: The need for unified constitutive models for frozen and unfrozen soils in simulating frost heave and thaw consolidation has been recognized. However, a reliable and easy‐to‐implement model is not yet available. This paper extends the one‐dimensional elasto‐plastic model proposed by Yu et al. to solve multi‐dimensional problems. In the extended model, total and effective stresses are taken as the stress variables for frozen and unfrozen soils, respectively. A critical‐state‐based mode, Clay And Sand Model (CASM), is employed for soil at unfrozen states. The emphasis is placed on how a basic constitutive model for unfrozen soils is extended to describe the elasto‐plastic behavior for both unfrozen and frozen soils in two steps: (1) extension of the constitutive model from unfrozen to frozen soils by considering ice‐bonding effect, and (2) integration of descriptions for soils at unfrozen and frozen states using the concept of residual stress (by Nixon and Morgenstern). The freeze‐thaw cycling effect is naturally incorporated by the introduction of residual stress line that is used to determine the initial stress state and preconsolidation pressure of thawed soil. After being implemented into FORTRAN subroutines for ABAQUS, the performance of the proposed model is demonstrated by simulating triaxial compression tests on frozen sand at different temperatures under confining pressures, and freeze‐thaw cycling processes of silty clay under loading.